2013
DOI: 10.1097/jsm.0b013e31829aef0f
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Prescribed Medication Use by the Finnish Paralympic and Olympic Athletes

Abstract: The use of any physician-prescribed medicines, especially those to treat chronic diseases, seems to be more common among the PAs than the OAs. Paralympic athletes use significantly less asthma medicines than OAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 16 publications
5
16
1
Order By: Relevance
“…The active pharmaceutical ingredient of each substance was identified to categorize the medication or supplement into one of the following: analgesia and anti‐inflammatory medications (NSAIDs, other analgesia, local anesthetics), muscle relaxants, respiratory agents, gastrointestinal medications, antimicrobial medications, antihistamines, supplements, and others. This classification is consistent with previous pharmacoepidemiologic studies in sport [6‐21].…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…The active pharmaceutical ingredient of each substance was identified to categorize the medication or supplement into one of the following: analgesia and anti‐inflammatory medications (NSAIDs, other analgesia, local anesthetics), muscle relaxants, respiratory agents, gastrointestinal medications, antimicrobial medications, antihistamines, supplements, and others. This classification is consistent with previous pharmacoepidemiologic studies in sport [6‐21].…”
Section: Methodssupporting
confidence: 91%
“…Previous research in able‐bodied athletes has revealed high and unexpected levels of medication use, especially of NSAIDs [6‐19]. In keeping with much of this research, NSAIDs were by far the most commonly used medication in disability footballers in our cohort, representing 39.3% of all medications used.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Understanding how pain is experienced by an athlete is important 280. Part of the socialisation of athletes in male sport includes a degree of (hyper)masculinisation, leading to efforts to disregard or downplay pain and injury 281.…”
Section: Ethical Issuesmentioning
confidence: 99%